2019
DOI: 10.5195/ledger.2019.177
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Services for New Paradigm Smart Cities Based on Decentralized Technologies

Abstract: This article describes different methods of organizing robotic services for smart cities using secure encrypted decentralized technologies and market mechanisms—as opposed to models based on centralized solutions based (or not) on using cloud services and stripping citizens of the control of their own data. The basis of the proposed methods is the Ethereum decentralized computer with the mechanism of smart contracts. In this work, special attention is paid to the integration of technical and economic informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In previous work of some of the authors, successful operation of several unmanned aerial vehicles on the Robonomics platform was demonstrated (Kapitonov et al, 2019 ); in the current research we are extending the approach to monitor the state of the environment, in particular of water quality. In this article we describe the operation of a small swarm of marine surface autonomous vehicles equipped with sensors in charge of performing water quality measuring, guided by a “leader” autonomous marine vessel managing a distributed secure registry of the samples by means of the Robonomics platform.…”
Section: Certified Samplingmentioning
confidence: 81%
See 2 more Smart Citations
“…In previous work of some of the authors, successful operation of several unmanned aerial vehicles on the Robonomics platform was demonstrated (Kapitonov et al, 2019 ); in the current research we are extending the approach to monitor the state of the environment, in particular of water quality. In this article we describe the operation of a small swarm of marine surface autonomous vehicles equipped with sensors in charge of performing water quality measuring, guided by a “leader” autonomous marine vessel managing a distributed secure registry of the samples by means of the Robonomics platform.…”
Section: Certified Samplingmentioning
confidence: 81%
“…The goal is to have a shared control network system integrating a bio-inspired swarm management into a secure distributed ledger. Previously some authors have proposed either pure blockchain solutions (Kapitonov et al, 2019 ) or swarm solutions (Strobel et al, 2018 ) where each node is a blockchain node (something that makes the swarm operation slow).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization (WHO) is considered coronavirus disease 2019 (COVID- 19) as an international pandemic epidemic on 11 March 2020. On 16 October 2020, WHO reported that the number of confirmed COVID-19 cases reached 38789204, and 1095097 confirm deaths [1].…”
Section: Introductionmentioning
confidence: 99%
“…With blockchain, independent robots can reach consensus without a central controller. Smart contracts provide great potential to enable more secure [17], autonomous, flexible, and even profitable [19] robotic operations [20]. Combating the COVID-19 outbreak requires automatic robots to collaborate with each other in a decentralized fashion without human intervention during task performance.…”
Section: Introductionmentioning
confidence: 99%